Mechanical performance of engineered cementitious composite containing crumb rubber at elevated temperature - Adamu M. (Institute of Physics Publishing, 2023)
Automotive industry; Compressive strength; Construction industry; Engineered cementitious composite; Rubber; Build-up pressure; Elevated temperature; Engineered cementitious composite (ECC); Environmental concerns; Explosive spalling; Mechanical performance; Research reports; Residual compressive strength; Rubber industry